Acolhimento como ferramenta para o cuidado humanizado na unidade de terapia intensiva neonatal - Soares, Larissa Gramazio (2014)
The role of welcoming as a guideline of the National Humanization Policy in the context of nursing care in the NICU process is provided by a descriptive survey, interventionist mode and a qualitative approach. Current study was conducted in a middle-size hospital in the interior of the state of Paraná, Brazil, more specifically in a NICU, between April and September 2014. It was divided into four phases: (i) thirteen parents were interviewed when the recently-born child was admitted into the NICU for more than five days; for data collection, a semi-structured scheme was given with the guiding question: "How does welcoming take place within nursing care in the context of NICU?" Interviews were recorded and transcribed in full (pre-test); (ii) the interventional phase (educational intervention) occurred through three educational workshops with the four NICU nurses in charge, by means of a problematizing methodology based on Charles Marguerez´s Arc. Testimonies collected in the first phase were the starting point. This process triggered a proposal of a pilot-protocol welcome for the NICU; (iii) the next month the nurses implemented the pilot-protocol welcome through a checklist recording the strong and weak points of the protocol during its execution; (iv) at the end of this period, the last meeting with the nurses occurred to analyze the difficulties and positive items encountered in the implementation of the welcome protocol. Further interviews with ten mothers and one father who, at this stage of research, were with their children in the intensive care unit, were conducted. The perception of the family after the deployment of the welcoming practice (post-test) was thus investigated. Results showed the effectiveness of educational strategies based on the problematization of care reality either through specific situations of attention scenarios as change proposals or in providing a sense of appreciation of professionals, who became protagonists of these transformations. In addition to operational issues, the study also revealed the importance of approach strategies for the qualification of welcome and, therefore, the care for the child-family binomial. Some strategies were the assigning of reference professionals for parents within the NICU environment; individualized / personalized preparation and orientation of families for the first visit to the child; optimization of the daily routine visit with information on the child´s evolution; inclusion of parents in the care of the newborn; and the preparation of parents for hospital discharge. Reflections on healthcare practices constitute an essential aspect to transform reality through the involvement of all the social agents within these contexts. In spite of the study´s limitations, current research experience plus its educational intervention opens the perspective for further studies and, at the same time, valorizes work partnership for health professionals and families for care practice.